Concentration of uranium and thorium in the product and by-productof amang and ilmenite tailings process - Husin Wagiran,; Lim , Say Eng; Lee , Siak Kuan; Mohamad Yasin Sudin, (Universiti Kebangsaan Malaysia, 2005)
Amang are by-products obtained when tailings are processed into concentrated ores and other economical products such as monazite, (Ce, La, Th)PO4; zircon, ZrSiO4; ilmenite, FeTiO3; struverit; and xenotime, YPO4. Its could be extracted from amang for further usage. Tailings from these ores may have a significant potential to cause elevated radiation exposures. This project was carried out to measure the concentration of uranium and thorium in the waste and products produced after the processing of the amang and ilmenite ore. The concentration of uranium and thorium was determined using gamma ray spectrometer with HPGe detector. The concentration of uranium was determined by measuring the intensity of gamma ray emitted from its daughter nuclei 214Pb at 352 keV and 214Bi at 609 keV while the concentration of thorium was determined by measuring the intensity of gamma rays emitted from its daughter nuclei 228Ac at 911 keV and 208Tl at 583 keV. The concentration of uranium and thorium in ppm obtained in this study are as follows: raw amang (83 -383) and (174 - 1566); ilmenite (149 - 290) and (301- 575); monazite (2303 - 4070) and (9641 – 60061); zircon (963 - 1192) and (353 - 583) and waste (22 - 98) and (44 - 223) respectively. Rutile and iron oxide was obtained from ilmenite. The concentration of uranium and thorium in rutile was 50 and 72 ppm and from iron oxide was 336 and 379 ppm respectively. These values are considered high compare to normal sand and could pose danger to the surrounding.